An Experimental and Theoretical Investigation on Pentacoordinated Cobalt(III) Complexes with an Intermediate S=1 Spin State: How Halide Ligands Affect their Magnetic Anisotropy. Issue 3 (26th November 2015) - Brazzolotto, Deborah; Gennari, Marcello; Yu, Shengying; Pécaut, Jacques; Rouzières, Mathieu; Clérac, Rodolphe; Orio, Maylis; Duboc, Carole
Abstract: Understanding the factors that control the magnitude and symmetry of magnetic anisotropy should facilitate the rational design of mononuclear metal complexes in the quest for single‐molecule magnets (SMMs), based on a single metal ion, with high blocking temperatures and large energy barriers. The best strategy is to define magnetostructural correlations through the investigation of a series of metal complexes. It has been demonstrated that the main contribution to the magnetic anisotropy arises from the spin‐orbit coupling (SOC) effect in metal‐ion‐based systems, so current studies focus particularly on the use of both ligands and metal ions possessing a large SOC. In this context, we report a unique series of halide Co III complexes, [CoL(X)], with X=Cl, Br, I (CoX ) and L=2, 2′‐(2, 2′‐bipyridine‐6, 6′‐diyl)bis(1, 1‐diphenylethanethiolate), which possess a rare intermediate S= 1 spin ground state. The S= 1 Co III complexes are attractive species because they possess a remarkably large axial zero‐field splitting (defined by D from the following Hamiltonian: H = DS z 2 ), as well as the halide ligands inducing large SOC constants. The single‐crystal X‐ray structures reveal that theCoBr andCoI complexes are isostructural with the previously describedCoCl complex. Their coordination sphere displays a distorted pentacoordinated square pyramidal geometry, with the halide located in the Co III axial position. Large positive D values of 35, 26, and 18 cm −1 are found forCoCl, CoBr, andCoI, respectively, through analysis of the magnetic susceptibility data as a function of temperature. To rationalize this trend, theoretical calculations based on both density functional theory (DFT) and complete active space self‐consistent field (CASSCF) methods are performed successfully. Both the sign and magnitude of D are predicted remarkably well by these theoretical approaches. The DFT calculations also show that the resulting D values originate from a balance of several contributions, and that many factors, including differences in their structural properties and in the contribution of the halide, should be taken into account to explain the trend of D in this series of complexes. Abstract : Complex magnetism : The factors that control the magnitude and symmetry of the magnetic anisotropy are investigated for a unique series of halide Co III complexes (see figure), which possess a rare intermediate S= 1 spin ground state and remarkably large axial zero‐field splitting.